My autobiography of Carson McCullers - Shapland, Jenn, 1987- (Tin House Books, 2020)
"While working as an intern in the archives at the Harry Ransom Center, Jenn Shapland encounters the love letters of Carson McCullers and a woman named Annemarie-letters that are tender, intimate, and unabashed in their feelings. Shapland recognizes herself in the letters' language-but does not see McCullers as history has portrayed her. And so, Shapland is compelled to undertake a recovery of the full narrative and language of McCullers's life: she wades through the therapy transcripts; she stays at McCullers's childhood home, where she lounges in her bathtub and eats delivery pizza; she relives McCullers's days at her beloved Yaddo. As Shapland reckons with the expanding and collapsing distance between her and McCullers, she sees the way McCullers's story has become a way to articulate something about herself. The results reveal something entirely new not only about this one remarkable, walleyed life, but about the way we tell queer love stories. In genre-defying vignettes, Jenn Shapland interweaves her own story with Carson McCullers's to create a vital new portrait of one of America's most beloved writers, and shows us how the writers we love and the stories we tell about ourselves make us who we are"--